Focus on the Role of D-serine and D-amino Acid Oxidase in Amyotrophic Lateral Sclerosis/Motor Neuron Disease (ALS) - Kondori, Nazanin R.; Paul, Praveen; Robbins, Jacqueline P.; Liu, Ke; Hildyard, John C. W.; Wells, Dominic J.; de Belleroche, Jacqueline S. (Frontiers in Molecular Biosciences, 2018)
We have investigated a pathogenic mutation in D-amino acid oxidase (DAO), DAOR199W, associated with familial Amyotrophic Lateral Sclerosis (ALS) that impairs D-serine metabolism and causes protein aggregation, autophagy and cell death in motor neuron cell lines. These features are consistent with the pathogenic processes occurring in ALS but most importantly, we have demonstrated that activation of the formation of ubiquitinated protein inclusions, increased autophagosome production and apoptotic cell death caused by the mutation in cell lines are attenuated by 5,7-dichlorokynurenic acid (DCKA), a selective inhibitor of the glycine/D-serine binding site of the NMDA receptor. D-serine is an essential co-agonist at this glutamate receptor. This data provides insight into potential upstream mechanisms that involve the action of D-serine at the NMDA receptor and might contribute to neurodegeneration. This is highly relevant to sporadic ALS (SALS), familial ALS, as well as ALS models, where elevated levels of D-serine have been reported and hence has broader clinical therapeutic implications. In order to investigate this further, we have generated a transgenic line expressing the pathogenic mutation, in order to determine whether mice expressing DAOR199W develop a motor phenotype and whether crossing the SOD1G93A model of ALS with mice expressing DAOR199W affects disease progression. We found that heterozygous expression of DAOR199W led to a significant loss of spinal cord motor neurons at 14 months, which is similar to that found in homozygous mice expressing DAOG181R. We hypothesise that DAO has potential for development as a therapeutic agent in ALS.